SEEDBANK AND SEEDLING EMERGENCE CHARACTERISTICS OF WEEDS IN RICEFIELD SOILS OF THE MUDA GRANARY AREA IN NORTH-WEST PENINSULAR MALAYSIA - MAHFUZA BEGUM; ABDUL SHUKOR JURAIMI; SYED OMAR OMAR BIN SYED RASTAN; RAJAN AMARTALINGAM; AZMI BIN MAN (SEAMEO BIOTROP, 2006)
Tlie experiment was conducted in the glasshouse of UPM from March 2003 to June 2004 to determine the soil seedbank in the ricefields ot'Muda rice granary area in Peninsular Malaysia. Six soil cores of 5 cm in diameter and 10 cm depth were sampled from each of 24 fields. All samples from each individual field were bulked and placed in plastic trays of 38 x 25 x 10 cm. Soil was moistened as required and emergence of weed seedlings were recorded over period of one year. After one year, remaining seeds were separated, removed and identified. The total seed bank was estimated at 1136.48 million/ha of which 62.35% (708.60 million seedlings ha